Photoluminescence properties and energy transfer investigations of Gd3+ and Sm3+ co-doped ZnO–BaO–TeO2 glasses for solid state laser application - N. Sangwaranatee (2020)
© 2020 Elsevier B.V. The physical, optical, photoluminescence properties of (54-x) TeO2 − 10ZnO − 35BaO − 1Sm2O3 − xGd2O3, where 0 ≤ x ≤ 3 (mol %) are investigated in this research. Five samples of glass were produced by the normal melt quenching process. The evidence indicates that the density of glass increased with increasing of Gd2O3. The molar volume and refractive index investigations have been used to consider the physical properties and optical properties of the produced glass system. Physical parameters such as polaron radius, inter-ionic radius and field strength for Sm3+/Gd3+ ions have been evaluated. The absorption spectra of glass contain peaks at 358, 404, 948, 1,085, 1,235, 1,385, 1490 and 1535 nm corresponding to the transitions from 6H5/2 to 4D3/2, 6P3/2, 6F11/2, 6F9/2, 6F7/2, 6F5/2, 6F3/2, and 6H15/2, respectively. The emission spectra of glass show four bands at found and attributed to 563, 604, 646 and 709 nm by excitation at 275 nm. Judd-Ofelt parameters and radiative properties was investigated for 53.5TeO2 − 10ZnO − 35BaO − 1Sm2O3 − 0.5Gd2O3 glass. Energy transfer characteristics was observed in the present glasses. The emission intensity of Sm3+ increased with increasing of Gd2O3 concentration until 2 mol %, while the luminescence lifetime decreases with increasing of Gd2O3 content.